Tortured Silence and Silenced Torture in Mario Benedetti's Pedro y el capitán, Ariel Dorfman's La muerte y la doncella and Eduardo Pavlovsky's Paso de dos - Gates-Madsen, Nancy J. (Latin American Theatre Review, 2008)
This essay examines the characterization of torturer and victim in three plays about state terrorism and torture in the Southern Cone. Given the inherent complexities involved in the practice and representation of torture, I argue that the portrayal of a stubbornly silent, heroic victim, especially when contrasted with a torturer who is all-too-human, risks converting victims into flat symbols of resistance instead of multidimensional characters. Furthermore, heroic representations of torture unwittingly reveal a disturbing reluctance to bear witness to uncomfortable truths about the slippery relationship between torture and betrayal and the power of radical evil. (NGM, Article in English)